MANAJEMEN LOGISTIK OBAT DI INSTALASI FARMASI RUMAH SAKIT AT-TUROTS AL-ISLAMY KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Feliza Triansyah; Wahyudiyono, Wahyudiyono (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2024)
Logistics management is part of an agency to provide the goods needed for the agency's operational activities in quantity, quality and at the right time (according to needs) at the lowest possible price. This study aims to determine the description of drug logistics management in the Pharmacy Installation of At-Turots Al-Islamy Hospital, Sleman Regency, Special Region of Yogyakarta. The method used is qualitative. Data collection was used by direct interviews, observation and documentation. The informants for this research were the Head of the Pharmacy Installation, Laksana Pharmacist, and Pharmaceutical Technical Staff (TTK). Data analysis uses the method described by Miles and Huberman. The results of the research explain that, budget planning is carried out once a month, planning for drug needs uses a consumptive and combination system, in the procurement section there are obstacles, namely empty distributors, rising prices, and an unexpected increase in the number of patients, in the storage section there are obstacles in recording remaining stock and unavailability of drug storage places that comply with standards. From this research it can be concluded that drug logistics management at the At-Turots Al-Islamy Hospital Pharmacy Installation has not been effective but not efficient due to various obstacles and has not met the standards set by the 2010 Ministry of Health Regulation.